A cognitive analysis of snake and lion metaphors in Mandarin Chinese and British English - Wei, Lixia (2012)
Not only are studies on animal expressions relatively few (Hsieh, 2004; Hsieh, 2006),but studies conducted cross-linguistically are scarce (Talebinejad and Dastjerdi, 2005). In addition, most previous studies on animal metaphors have been based on data collected from dictionaries or surveys and they have focused on the aspect with human beings as the target domain. This study is an effort to add to findings of the previous studies. Based on the Conceptual Metaphor Theory (CMT) and the Conceptual Blending Theory (CBT), this study investigated snake and lion metaphors based on data collected from authoritative corpora in Mandarin Chinese and British English. Another added dimension of the study is the target domain includes both human beings and non-human beings. The main aim of the study was to identify similarities and differences between snake and lion metaphors in the two languages. Six steps were involved in the collection and analysis of the data. First, the data comprising snake and lion expressions in Mandarin Chinese and British English were collected from the Modern Chinese Corpus compiled by the Centre for Chinese Linguistics of Peking University (CCL Corpus) and the British National Corpus (BNC) respectively. Then, the snake and lion metaphorical expressions were identified. Next, the metaphorical expressions were categorized according to their source domains and target domains. Meanwhile, the evaluation of each metaphorical expression was ascertained. Subsequently, particular metaphors were generalized from the data. Following that, the CMT and the CBT were applied to the interpretation of typical metaphorical expressions and metaphors. Finally, the results obtained from the two languages were compared. Both similarities and differences between the snake and lion metaphors in Chinese and English were found. In terms of similarities, first, the animal’s characteristic and appearance are the main aspects of the source domain when the target domains are human beings and non-human beings respectively. Second, human beings, daily items, and economy are the three main shared target domains. Third, more conceptual metaphors were generalized for human beings than any non-human domains. Fourth, the conceptual metaphors generalized from the animal’s appearance are image-based, from the animal’s behavior are both image-based and knowledge-based, and from the animal’s characteristic are knowledge-based. In terms of differences, first, the animal expressions can be mapped onto more domains in Chinese than in English and more conceptual metaphors were generalized in Chinese than in English. Second, the snake metaphorical expressions have a much more derogative meaning of man in Chinese but a much more derogative meaning of woman in English. Third, the lion metaphorical expressions convey more negative meaning in Chinese than in English when they were applied to woman. Moreover, this study also found support for Kövecses’s (2002; 2005; 2010) claim that both cultural contexts and the natural and physical environment play a role in explaining the causes for metaphor universality and variation in Chinese and English. Thus, the study on snake and lion metaphors provides evidence to show that universality and variation between animal metaphors exist in Chinese and English. Apart from its contribution to the literature on studies of animal metaphors, the findings from this study seem to have modified Kövecses’s (2002, 2010) dichotomy categorization of metaphors by adding another type, that is metaphors that are both image and knowledge-based at the same time. The findings from this study also have some contribution in terms of refining the CBT. In this case, a revised version of the CBT is obtained by allocating more attention to context in the process of interpreting metaphorical expressions and metaphors and by adding a new space, that is, the output space. Keywords: metaphor, snake metaphors, lion metaphors, Mandarin Chinese, British English, Conceptual Metaphor Theory, Conceptual Blending Theory.